Proposal for the Design of Cultural Tourist Routes through the Use of GIS: An Applied Case - Calderón-Puerta, Diego Manuel; Arcila-Garrido, Manuel (Revista de Estudios Andaluces, 2020)
Cultural tourism routes and itineraries are tourism promotion tools that have undergone a remarkable development in recent years, thanks to their ability to enhance the value of cultural heritage. In this sense, national and international organizations as well as private initiatives have designed tourist routes that cover a wide range of topics, while cultural itineraries have been recognized at the institutional level by organizations such as ICOMOS or the Council of Europe. The main objective of this article is to offer a proposal for the design of cultural tourist routes through the use of a geographic information system. To achieve this goal, we start from a brief theoretical framework in which the tourist use of geographic information systems and the conceptualization of tourist routes and their differences with itineraries are analyzed. Subsequently, the methodology used consists of two distinct phases. Initially, a quantitative study is carried out in which data on the late medieval heritage are collected and subsequently, through the use of a GIS, an index of tourist potentiality is carried out and the creation of a tourist route in the province of Cádiz (Spain). In this way the results obtained justify the route designed and the choice of municipalities, based on their greater availability of tourism resources (accessibility, hospitality etc.) and cultural (historical assets). With all this is intended the activation of a heritage that has notorious possibilities for tourism and cultural promotion, based on the common history they share and that is forged over more than two centuries.